Robotic Extrusion of Algae‐Laden Hydrogels for Large‐Scale Applications (Global Challenges 1/2020). Issue 1 (6th January 2020) - Malik, Shneel; Hagopian, Julie; Mohite, Sanika; Lintong, Cao; Stoffels, Laura; Giannakopoulos, Sofoklis; Beckett, Richard; Leung, Christopher; Ruiz, Javier; Cruz, Marcos; Parker, Brenda
Abstract : In article number 1900064 by Marcos Cruz, Brenda Parker, and co‐workers, a 1000 × 500 mm fibrous panel is robotically extruded from alginate‐based hydrogels immobilized with microalgal cells. Additively deposited layer by layer with three different hydrogels with varying water percentages, the biocompatible scaffold is hierarchically constructed and has mechanical stability. This bioprinting technique demonstrates the potential of creating large‐scale biohybrid structures for applications such as bioremediation within architecture and the built environment.